Biodegradable jute cloth reinforced thermoplastic copolyester composites: Fracture and failure behaviour - Acha, Betiana Andrea (2006)
Jute cloth reinforced, fully biodegradable thermoplastic composites were produced by the film stacking technique, with a semicrystalline copolyester (Ecoflex) as the matrix material. The jute cloth content varied between 0, 20 and 40 wt-% in the sheets produced by hot pressing. Specimens cut from the sheets were subjected to in plane static and out of plane dynamic loading, and the related fracture and failure behaviours were studied. The jute cloth proved to be a useful reinforcement to enhance in plane mechanical properties. The J integral concept (J-R curve) was adopted to assess the fracture behaviour of the composites. Crack propagation in single edge notched tensile (SEN-T) loaded specimens was detected using position resolved acoustic emission (AE). Acoustic emission was also used to characterise the failure. Surprisingly, no beneficial effect of the jute cloth was observed in the out of plane, namely instrumented falling weight impact (IFWI) test. This could be explained by the characteristics of the jute cloth used (the large mesh size increases the tendency to disintegrate when stretched at high strain rates) and by its moderate adhesion toward the matrix. © 2006 Institute of Materials, Minerals and Mining.